Evaluation of the Correlation between Particulate Matter (PM2.5) and Meteorological Parameters - Hamdan, Nur Hidayah Rosman; Hamdan, Rafidah; Hamdan, Wesam A.Y. Al Madhoun (Journal of Advancement in Environmental Solution and Resource Recovery, 2021)
Particulate matters are emitted from a wide range of man-made and natural sources. Particulate matters (ð‘ƒð‘€2.5) pose the greatest problems and consequences to human health. Batu Pahat is considered as main urban area with high industrial activity and other anthropogenic activities. Due to awareness of the people health in Batu Pahat this study was performed. The focus of this research is to examine the levels of ð‘ƒð‘€2.5 in several areas in Batu Pahat and to examine the correlations of ð‘ƒð‘€2.5 with the weather parameters using the Pearson correlation coefficient. Two stations of selected areas were chosen, namely Batu Pahat, and Parit Sulong represented as an urban area, and residential area. Three parameters observed for 3 consecutive months starting from December 2020 to February 2021 in two phases which were phase 1 (7a.m.) and phase 2 (7p.m.). The data was obtained from the website of Department of Environment (DOE). The statistical analysis of the results obtained for the air particulate matters ð‘ƒð‘€2.5 at the study areas will be compared with the Malaysian Ambient Air Quality Guidelines (MAAQG). It was found out that the concentration of ð‘ƒð‘€2.5 at station B (Parit Sulong) the residential area, was higher in phase 1 and phase 2 with value of 15.04 Î¼g/ð‘š3 and 14.12 Î¼g/ð‘š3 respectively. It can be seen that station B have higher value of ð‘ƒð‘€2.5 than station A (Batu Pahat). Air quality index (AQI) values for both stations was less than the permitted value by Malaysian Ambient Air Quality Guidelines.